2015
DOI: 10.1159/000441852
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy in a European Cohort of 1,147 Patients with IgA Nephropathy

Abstract: Background: Tonsillectomy has been considered a treatment for IgA nephropathy (IgAN). It is aimed at removing a source of pathogens, reducing mucosa-associated lymphoid tissue and decreasing polymeric IgA synthesis. However, its beneficial effect is still controversial. In Asia, favorable outcomes have been claimed mostly in association with corticosteroids. In Europe, small, single-center uncontrolled studies have failed to show benefits. Methods: The European validation study of the Oxford classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 26 publications
1
54
0
1
Order By: Relevance
“…Tonsillectomy combined with steroid pulse therapy induced a 10% greater decrease in proteinuria than steroid pulse therapy alone, but this decrease was of marginal statistical significance, and whether it would lead to a subsequent beneficial effect on renal function is unclear. Consistent with the Japanese trial, a comparison of tonsillectomized patients with IgAN and non-operated matched controls with IgAN assessed in a study performed by the European VALIGA network failed to show any effects of tonsillectomy on circulating markers of innate immunity, ubiquitin-proteasome pathways and the pro-oxidative milieu 87 , or on clinical outcome 88 .…”
Section: Other Mucosal Diseasesmentioning
confidence: 63%
“…Tonsillectomy combined with steroid pulse therapy induced a 10% greater decrease in proteinuria than steroid pulse therapy alone, but this decrease was of marginal statistical significance, and whether it would lead to a subsequent beneficial effect on renal function is unclear. Consistent with the Japanese trial, a comparison of tonsillectomized patients with IgAN and non-operated matched controls with IgAN assessed in a study performed by the European VALIGA network failed to show any effects of tonsillectomy on circulating markers of innate immunity, ubiquitin-proteasome pathways and the pro-oxidative milieu 87 , or on clinical outcome 88 .…”
Section: Other Mucosal Diseasesmentioning
confidence: 63%
“…We are aware of limited potential for generalization of conclusions made from our study cohort but it needs to be highlighted that not only the size of the cohort but also the racial and regional factors could influence the clinical value of measured parameters. For example, tonsilectomy performed in cohort of 200 Japanese IgAN patients [38] showed beneficial effect on IgAN course but this was not proven in European cohort of 61 tonsillectomized IgAN subjects selected from large cohort of 1, 147 VALIGA subjects [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the report by Chen et al [28], with a follow-up period of 11 years, showed a negative result, they mentioned in their discussion section that ‘perhaps a longer follow-up might reveal a statistical significant difference’. Recently, Feehally et al [29] reported that no significant correlation was found between tonsillectomy and a decline in renal function over a follow-up of 4.7 years in the VALIGA cohort. On the basis of the previous reports, a longer follow-up may be needed for a more proper evaluation.…”
Section: Discussionmentioning
confidence: 99%